The art of modern conjuring for wizards of all ages - Garenne, Henri (New York Clarkson Potter, 2001)
Perfect for novice or armchair magician with more than 200 astounding tricks from basics to more difficult tricks using vintage engravings.
Originally published: London : Ward, Lock, and Co., 1886.
112201
Keywords: Magic tricks; Conjuring; Prestidigitation